2004
DOI: 10.1093/bja/aeh106
|View full text |Cite
|
Sign up to set email alerts
|

Rocuronium for muscle relaxation in two children with Friedreich's ataxia

Abstract: Friedreich's ataxia is a rare hereditary neurodegenerative disease caused by a defect in the gene that encodes a mitochondrial protein called frataxin. We report the use of rocuronium 0.6 mg kg(-1) in two adolescent girls with Friedreich's ataxia undergoing propofol-sufentanil-oxygen-air anaesthesia for spinal surgery. Neuromuscular transmission was monitored using acceleromyography, and onset and recovery times were recorded. The clinical duration of rocuronium was comparable to that of children without neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 9 publications
2
15
0
2
Order By: Relevance
“…Schmitt et al, on the other hand, used total intravenous anesthesia with propofol and sufentanil instead of volatile anesthetics for maintenance of anesthesia and reported no delay in recovery with rocuronium. After they used recuronium bromide uneventfully in the anesthesia of two patients diagnosed with FA, they reported that nondepolarizing muscle relaxants might be used safely in patients with FA [6]. Although no complications were reported in the majority of those studies, it is not possible to guarantee safe use of various drugs (such as muscle relaxants), since none of them have been studied with high power and randomization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schmitt et al, on the other hand, used total intravenous anesthesia with propofol and sufentanil instead of volatile anesthetics for maintenance of anesthesia and reported no delay in recovery with rocuronium. After they used recuronium bromide uneventfully in the anesthesia of two patients diagnosed with FA, they reported that nondepolarizing muscle relaxants might be used safely in patients with FA [6]. Although no complications were reported in the majority of those studies, it is not possible to guarantee safe use of various drugs (such as muscle relaxants), since none of them have been studied with high power and randomization.…”
Section: Discussionmentioning
confidence: 99%
“…Pancora et al reported that due to the hypersensitivity of FA patients to non-depolarizing muscle relaxants, muscle relaxants might potentially cause delays in recovery and discharge, and hence they facilitated the intubation of the patients with the use of propofol and sufentanil without the use of muscle relaxants. They used optimal drug infusion (remifentanil and propofol) during maintenance anesthesia by providing a bispectral index value of 45-60 [6].…”
Section: Discussionmentioning
confidence: 99%
“…Schmitt et al showed that the rocuronium recovery times of patients with FA were similar to those without any neuromuscular disease [7].…”
Section: Casementioning
confidence: 98%
“…There is an increased response against hyperkalemia that might occur following succinylcholine usage in such patients, which can result in cardiac arrhythmia. Hence, depolarizing muscle relaxant use should be avoided [7]. Tubocurarine hypersensitivity was stated earlier in an old case presentation [8].…”
Section: Casementioning
confidence: 99%
See 1 more Smart Citation